64 Seizing an Opportunity: Setting Up A Virtual Wetlab During the COVID19 Pandemic. (12th October 2021) - Holland, L; Ahmed, I
Abstract: Aim: The COVID19 pandemic has negatively impacted surgical training across the globe. In the UK, educational events and training days were cancelled for trainees at all levels. However, these unusual times provide opportunity to develop novel teaching methods. Our aim was to design a "virtual cardiac surgery wetlab" that allows real-time skills training. Method: With support from industry partners Edwards Lifesciences, Wetlab and Connexon365 (Webinar Hosting Platform) all the necessary materials were distributed. A package was sent to trainer and trainees that included microinstruments, sutures, synthetic vessels and valve models, high-definition camera, along with printed instructions and video to outline set-up of the rig. Trainees only need to provide is a computer. A consultant surgeon demonstrated how to perform a coronary anastomosis and aortic valve replacement and was then able to supervise trainees and provide real-time feedback using the online platform. Results: Feedback from trainer and trainees has shown that the system is an easy-to-set-up, effective training tool for teaching cardiac surgery skills including coronary anastomosis and valve surgery. The online platform enabled good vision and engagement between trainer and trainee and also enabled recording of the session. Distributing all of the materials nationwide means the virtual wetlab can take place anywhere, including in the comfort of home, for both trainee and trainer. Conclusions: Surgical skills training can still take place effectively in the absence of "real life" wetlabs. Given the current COVID19 pandemic continues to interrupt traditional surgical teaching, this method has potential to be adopted nationwide to minimise the disruption.